Activity Combination of Lime Juice (Citrus aurantifolia Swingle), Pickle Tree (Averrhoa bilimbi L.) and Garlic (Allium sativum L.) Against Growth of Propionibacterium acnes In Vitro - Novia Lestiandari; Samingan Samingan; Iswadi Iswadi; Wiwit Artika; Khairil Khairil (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Propionibacterium acnes. Plants that have the potential as a natural antibiotic can be found in various types of plants, including lime, pickle tree, and garlic. The purpose of this study was to determine the antibacterial activity of the combined concentration of lime juice, pickle tree and garlic on the growth of Propionibacterium acnes, and see the most effective concentration of the combination of juice. The approach used in this study was quantitative, an experimental method using a non-factorial randomized design (RAL) pattern consisting of 11 treatment groups and 3 replications. Data were analyzed using Variant Analysis (ANOVA) and Duncan's Nearest Real Distance Test (JNTD) at a significant level of 0.05. The results showed that there were significant differences between variations in concentration and single variations. The most effective juice concentration combination is a combination of juice 100% with an average inhibition diameter of 12.68 mm. Keywords: Inhibitory zone, a combination of extracts, Propionibacterium acnesJerawat merupakan kondisi dermatologis umum yang disebabkan oleh Propionibacterium acnes. Tumbuhan yang memiliki potensi sebagai antibiotik alami dapat ditemukan pada beragam jenis tumbuhan, diantaranya jeruk nipis, belimbing wuluh, dan bawang putih. Tujuan dari penelitian ini adalah untuk mengetahui aktivitas antibakteri kombinasi konsentrasi perasan jeruk nipis, belimbing wuluh, dan bawang putih terhadap pertumbuhan Propionibacterium acnes, serta melihat konsentrasi paling efektif dari kombinasi perasan. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kuantitatif, metode eksperimental menggunakan pola Rancangan Acak Lengakap (RAL) non faktorial yang terdiri dari 11 kelompok perlakuan dan 3 kali ulangan. Data dianalisis dengan menggunakan Analisis Varian (ANOVA) dan uji lanjut Jarak Nyata Terdekat Duncan (JNTD) pada taraf signifikan 0,05. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang bermakna antara aktivitas variasi kombinasi konsentrasi maupun variasi tunggal. Kombinasi konsentrasi perasan paling efektif ialah kombinasi perasan 100% dengan rata-rata diameter hambat 12,68 mm.. Kata Kunci: Zona hambat, kombinasi ekstrak, Propionibacterium acnes